Letter from Georg Bredig to Max Bredig, April 19, 1937 - Bredig, Georg (1937)
In a letter to his son Max Bredig (1902-1977), Georg Bredig (1868-1944) suggests that Max should settle a dispute with his supervisor amicably to avoid any potential negative consequences for his professional life. He also mentions that Max may eventually need to emigrate and advises him to become more self-reliant. Georg concludes by discussing his desire to travel to Switzerland during the upcoming summer and spend his vacation with his children.
Keywords: Conflict management; Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977; Vacations